BUDDHIST POETRY AS DIGITAL PRACTICE A HERMENEUTIC APPRO ACH TO THEMATIC AND SOCIO-SPIRITUAL FUNCTIONS IN INDONESIA - Latifah Latifah (TELL - US JOURNAL, 2026)
Buddhist poetry has a rich tradition as a medium for spiritual expression and instruction across diverse cultures. In the digital age, this tradition has found a new arena for evolution and adaptation. This study aims to analyze the thematic evolution and socio-spiritual functions of Buddhist poetry within the Indonesian digital space. Employing a digital hermeneutic approach with a scaled reading method reading (van de Ven & van Nuenen, 2022), this research examines the production, dissemination, and reception of Buddhist poetry across six online platforms personal blogs, community blogs (Kompasiana), Buddhist organizational sites (tisarana.net, PERGABI YouTube), social media (TikTok), and content-sharing sites through three analytical levels: platform hermeneutics, distant reading to map thematic patterns, and close reading of selected poetic texts.The findings reveal that Indonesian digital Buddhist poetry maintains its contemplative core while developing three key interrelated functions: (1) an innovative medium for digital Dharma education from poetry as doctrinal learning on to multimodal learning resources on PERGABI YouTube; (2) a platform for reflecting on and responding to contemporary social issues, including inner struggle, grief, and ethical crises reinterpreted through canonical narratives such as Kisagotami and Devadatta; and (3) a space for negotiating Buddhist identity within a Muslim-majority context, both through conscious identity affiliation on secular platforms (Kompasiana) and digital ritual practices that build implicit communities on TikTok. Cross-platform analysis demonstrates how the distinctive features of digital media hypertextuality on blogs enabling doctrinal interconnection, multimodality on YouTube integrating text, sound, and ritual imagery, and algorithmic visibility on social media shaping the circulation of religious content fundamentally reshape poetry's function as ritual practice and community building, giving rise to what may be termed "networked Dhamma."This study concludes that digital Buddhist poetry in Indonesia represents a dynamic synthesis of traditional spiritual expression and contemporary digital adaptation, successfully bridging personal spiritual practice with collective engagement while maintaining doctrinal integrity. These findings offer a conceptual framework for understanding the transformation of religious literature and practice in increasingly digitalized societies.